Ultrasound Biomicroscopy Observation of Suspicious Primary Angle Closure Combined with the Relaxation of Zonule. (8th March 2022) - Ma, Jingjing; Jiang, Nan; Jiang, Zhongtai; Lin, Jing; Li, Cui; Zhao, Guiqiu
Abstract : Purpose . To investigate the difference in anterior segment parameters between suspicious primary angle closure (PACS) patients and normal patients as assessed by ultrasound biomicroscopy (UBM). Methods . From June 2019 to November 2020, 39 patients (50 eyes) with PACS in the Ophthalmology Department of Qingdao University Affiliated Hospital who underwent phacoemulsification and intraocular lens implantation were selected as the PACS group. 32 patients (50 eyes) who underwent phacoemulsification and intraocular lens implantation were selected as the normal group. In addition to routine preoperative examinations such as visual acuity, noncontact intraocular pressure, axis length (AL), and ocular B-ultrasound examination, UBM examinations were also performed, including measuring the central anterior chamber depth (ACD), the maximum transverse diameter of the ciliary process at both ends (STS), the vertical distance between the anterior apex of the lens and the maximum transverse diameter at both ends of the ciliary processes (h), and angle opening distance (AOD500), iris-zonule distance (IZD), trabecular-ciliary process distance (TCPD), trabecular-iris angle (TIA), iris thickness (IT), trabecular-ciliary process angle (TCPA), and anterior placement of the ciliary body (APCB) at four quadrants (superior, nasal, inferior, and temporal quadrants). Results . Compared with the normal group, the PACS group showed statistically differences in AL, ACD, h, ACD/AL, h/STS, IZD, AOD500, TCPD, TIA, TCPA, and APCB (P < 0.05 ), and there were no significant differences in STS and IT between the two groups (P > 0.05 ). In the PACS group, there were significant differences in AL, ACD, h, ACD/AL, h/STS, IZD, TCPD, TCPA, and APCB between PACS patients with zonular relaxation and without zonular relaxation (P < 0.05 ), while there were no significant differences in STS, AOD500, TIA, and IT (P > 0.05 ). Conclusion . UBM quantitatively enables to identify the anterior segment morphology, especially the zonules in patients of suspicious primary angle closure combined with the relaxation of zonule. Accurate measurement of UBM can be used to predict whether patients with PACS are combined with zonular relaxation, so as to provide a clinical imaging evidence for the diagnosis.